Liberalizing and Re-Regulating Telecommunications in Europe: A Common Framework and Persistent Differences - Peter Holmes; Alasdair R. Young (Hamburg Institute of International Economics (HWWA), 2002)
This paper analyses the role of the European Union in promoting liberalisation among its member states and in crafting the multilateral regime for telecommunications services. It begins by analysing the origins of the EU regime, describing its contours and assessing its implementation. It then examines the interaction between the EU and the multilateral regime, examining the Uruguay Round and post-Uruguay Round negotiations on telecommunications services and outlining the issues under consideration in the GATS 2000 negotiations. It then proceeds to assess how the regulatory developments at the national, European and multilateral levels coexist and interact. – – Dieses Papier analysiert die Rolle der Europäischen Union bei der Liberalisierung der Telekommunikationsmärkte ihrer Mitgliedstaaten und bei der Formung des multilateralen Regimes für Telekommunikationsdienstleistungen. Es beginnt mit einer Darstellung der Ursprünge des EU-Regimes, beschreibt seine Merkmale und beurteilt seine Umsetzung. Dann untersucht das Papier die Zusammenhänge zwischen dem EUund dem multilateralen Regime, analysiert die Uruguay-Runde und die Folgeverhandlungen bezüglich der Telekommunikationsdienstleistungen und skizziert einige Themen der neuen GATS 2000-Runde. Schließlich beschäftigt es sich mit der Frage, wie die nationalen, europäischen und multilateralen Entwicklungen bei der Regulierung der Telekommunikationsmärkte verlaufen und wie sie aufeinander einwirken.
Keywords: L96; F02; F13; 330; International Economic Order; European Union; Trade Negotiations; Telecommunications; Telekommunikationspolitik; Deregulierung; Internationaler Dienstleistungsverkehr; Verhandlungen; WTO-Regeln; EU-Staaten